Impact of salinity stress on fruit quality of different Mediterranean cherry-type tomato landraces - Ntanasi, Theodora; Ntatsi, Georgia; Karavidas, Ioannis; Ziogas, I.; Karaolani, M.; Fortis, Dimitrios; Zioviris, Georgios; Fotopoulos, Vasileios; Schubert, Andrea; Guillaume, M.; Causse, Mathilde A.; Conesa, Miquel Àngel; et al. (My University, 2023)
Abiotic stresses, such as salinity, pose major risks on sustainability and productivity of most vegetable crops in the Mediterranean Basin. In soilless cultivation systems, mild salinity stress is introduced as a common practice to improve the organoleptic characteristics of tomato fruit, compromising at the same time crop production. In this study, we aimed to identify the impact of the salinity stress on the fruit quality of seven cherry-type tomato landraces (namely 'tomataki', 'GR-451/04', 'CC-1791 Allungato a Fiasco', 'Cherry-INRAE (1)', 'Cherry-INRAE (2)', 'Cherry-INRAE (3)', 'Cherry-INRAE (4)'). The experiment was conducted at the greenhouse facilities of the Laboratory of Vegetable Production at the Agricultural University of Athens. To apply the stress factor, the plants were grown under 30 mM NaCl in the nutrient solution versus the non-saline treated plants that were irrigated with a nutrient solution containing 0.5 mM NaCl. Fruit quality parameters such as diameter, firmness, titratable acidity (TA) and total soluble solids content (TSSC) were assessed. According to the main findings of this study, no reduction in the fruit quality characteristics of the landraces 'Cherry-INRAE (1)', 'Cherry-INRAE (2)' and 'Cherry-INRAE (3)' when exposed to salinity was observed. Salt stress improved the fruit firmness, TSSC and TA of the Greek landrace 'GR 451/04' while reduced its fruit diameter. On the contrary, increased salinity in the nutrient solution did not affect the diameter of fruit for landrace 'Cherry-INRAE-4', while led to increased concentrations of TSSC in fruit. The identified tolerant and resistant landraces could potentially be used in breeding programs to develop new cultivars and hybrids that can better adapt in saline-affected environments.
Keywords: abiotic stress; fruit quality; landraces; salinity stress; soilless culture; tomato